Comparison of Critical Thinking Ability and Metacognitive Skills on PPG PAI Learning Outcomes - Tola, Baso; N. Hula, Ibnu Rawandhy; Pateda, Lamsike; Mariana, Ana (Jurnal Pendidikan Indonesia, 2025)
The development of critical thinking and metacognitive skills is an important focus in professional teacher education, including in the Islamic Religious Education Teacher Professional Program (PPG PAI). However, there are still limited studies comparing the relative contribution of these two skills to the learning outcomes of prospective teachers. This study aims to analyze the significance of the role of critical thinking and metacognitive skills in shaping PPG PAI learning outcomes. This study used a quantitative research design with a correlational approach. Data were collected from 60 participants across two cohorts selected by purposive sampling. The data collection method was through tests. The research instrument was an integrated essay test. The data analysis technique used was inferential statistical analysis, analyzed through multiple linear regression. The results showed a statistically significant relationship (F = 12.828, p < 0.001) with a combined contribution of 28.6% of both variables to learning outcomes. Critical thinking had a slightly greater influence (Beta = 0.478) than metacognition (Beta = 0.499). This finding emphasizes the need for an integrated strategy for developing both skills in the PPG PAI curriculum to improve prospective teachers' reflective and analytical competencies. The implications of this research are relevant for improving teacher education programs to be more responsive to the needs of contemporary Islamic education.